Pembatasan Masa Jabatan Pejabat Dua Periode Dalam Perspektif Fiqh Siyasah - Hazizah Hasibuan; Erna Susanti; Sabila Alhakim; Rahman; Riski Nasution; Rahayu Pratiwi (Albayan Journal of Islam and Muslim Societies, 2024)
Abstract: This paper discusses the relationship between the duties and objectivess of the state in fiqh siyasah and the two-term presidential system. In fiqh siyasah, the state's duties are outlined as efforts to establish order, promote the welfare of the people, maintain defense and security, and uphold justice. The ultimate goal of the state is to achieve the happiness of its citizens, which requires stable and sustainable leadership. A two-term leadership tenure can be seen as a solution to ensure that leaders have sufficient time to plan and implement long-term policies without being hindered by excessive political dynamics. In this context, effective leadership over two terms allows a state to achieve its objectives, such as social welfare, legal order, and security, through policy consistency and governance continuity. Thus, the two-term system can be viewed as a means to achieve the broader goals of the state, providing leaders the opportunity to fulfill their duties effectively and address existing challenges. The restriction of positions in two periods is also in accordance with the principles of fiqh siyasah to minimize the occurrence of absolute, corrupt and arbitrary power.   Abstrak: Tulisan ini membahas hubungan antara tugas dan tujuan negara dalam fiqh siyasah dan sistem presidensial dua periode. Dalam fiqh siyasah, tugas negara digariskan sebagai upaya untuk membangun ketertiban, memajukan kesejahteraan rakyat, menjaga pertahanan dan keamanan, serta menegakkan keadilan. Tujuan akhir negara adalah untuk mencapai kebahagiaan warganya, yang membutuhkan kepemimpinan yang stabil dan berkelanjutan. Masa jabatan kepemimpinan dua periode dapat dilihat sebagai solusi untuk memastikan bahwa para pemimpin memiliki waktu yang cukup untuk merencanakan dan menerapkan kebijakan jangka panjang tanpa terhalang oleh dinamika politik yang berlebihan. Dalam konteks ini, kepemimpinan yang efektif selama dua masa jabatan memungkinkan negara untuk mencapai tujuannya, seperti kesejahteraan sosial, ketertiban hukum, dan keamanan, melalui konsistensi kebijakan dan kontinuitas tata kelola. Dengan demikian, sistem dua periode dapat dipandang sebagai sarana untuk mencapai tujuan negara yang lebih luas, memberikan kesempatan kepada para pemimpin untuk memenuhi tugas mereka secara efektif dan mengatasi tantangan yang ada. Pemberlakuan jabatan dalam dua periode juga sesuai dengan prinsip fiqh siyasah untuk meminimalisir terjadinya kekuasaan yang absolut, korup, dan sewenang-wenang.